Method for improving color difference of concrete by using regenerated micro powder loaded with chemical admixture and concrete prepared by using regenerated micro powder
By using regenerated micropowders loaded with chemical admixtures in concrete, the problem of color difference in concrete appearance is improved, and the color consistency of concrete structure and the resource utilization of construction solid waste are achieved.
Patent Information
- Application Number
- CN202411708367.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to effectively improve the color difference of concrete appearance, which affects the inner and outer beauty of concrete structures.
By loading sodium alginate and melamine with recycled micropowder after carbonization of waste concrete, it acts on the plastic changes of concrete and cement hydration stages, reducing early and later water secretion and promoting uniform distribution of moisture and solid phase.
Significantly improve the appearance color difference of concrete after demolition, improve overall color consistency, and promote the resource utilization of construction solid waste.
Smart Images

Figure CN119661115A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a method for improving concrete color difference by using recycled micropowder loaded with chemical admixtures and concrete prepared by using the same. Background Art
[0002] With the continuous development of my country's new urbanization and urban modernization construction, as well as the steady implementation of urban renewal, the demolition of old buildings has generated a large amount of construction solid waste, of which waste concrete accounts for up to 60%. Actively exploring the resource utilization of waste concrete has become an urgent and major need. In addition, the continuous maturity of urbanization development has made people no longer satisfied with the function of buildings being only solid and durable. Rough and simple concrete structures are increasingly required to be given aesthetic meanings. However, color difference in appearance is a common and difficult-to-solve problem in concrete preparation, which seriously affects the inner and outer beauty of concrete structures. In recent years, the increasing complexity of the source of concrete raw materials has aggravated the problem of concrete color difference caused by mixture segregation and bleeding.
[0003] The formation of color difference in the appearance of concrete, which is of general significance, comes from the uneven distribution of phases inside the concrete, and the uneven color depth of the concrete surface is mainly affected by the distribution of cementitious materials, hydration products and water on a macro scale. Therefore, the key to improving the color difference of the appearance of concrete lies in promoting the uniform dispersion of the above three types of substances, especially water. However, as a multi-phase and multi-component mixture, the distribution and evolution of its internal phases are accompanied by the entire process of hydration of cementitious materials since mixing. It is particularly difficult to improve the color difference of concrete without changing the composition of concrete on a large scale.
[0004] Patent CN 114149193 A discloses a method for controlling water marks and color difference on the surface of plain concrete and the obtained plain concrete. The method realizes the control of water marks and color difference on the surface of plain concrete by adopting amphiphilic active water mark shielding technology and compressed silica micropowder slurry redispersion technology. The amphiphilic active water mark shielding technology constrains and solidifies the components forming water marks inside the concrete during the concrete forming stage to realize water mark shielding; the compressed silica micropowder slurry redispersion technology increases the surface wettability and produces the same ion repulsion effect, and produces a synergistic effect with the ether modifier to realize the effective dispersion of lightweight admixtures in low water-cement ratio concrete slurry, thereby improving the consistency of the color of the plain concrete surface and avoiding the formation of water marks and color difference on the plain concrete surface.
[0005] Patent CN 114560663 A discloses an ultra-low color difference concrete based on heavy calcium powder and a preparation method thereof. Through reasonable proportion design, the poured concrete has a uniform appearance and color, is free of bubbles, and has a very good finishing effect. It can achieve the effect of plain concrete without modification, which not only meets the finishing effect of bridge structures, but also provides a high value-added utilization of heavy calcium powder and granulated blast furnace slag powder solid waste; reduces cement consumption and thus reduces carbon emissions, and prepares low-carbon concrete; in the three-phase system of heavy calcium powder, granulated blast furnace slag powder and cement, machine-made sand can be used in bridge facing concrete with a higher concrete appearance, further broadening the application range of machine-made sand.
[0006] Patent CN 107365120 A discloses a concrete cementitious material, a high-durability plain concrete and a preparation method thereof. The high-durability plain concrete removes fly ash and, through the incorporation of fine beads and microsilica powder, reduces the average bubble chord length, increases the density, eliminates the color difference problem of the plain concrete appearance caused by fly ash, reduces the appearance bubbles, improves the durability, and meets the requirements of high-durability plain concrete. Summary of the invention
[0007] In view of a series of problems such as color difference caused by uneven distribution of internal phases in the existing technology, the present application proposes a method for improving the color difference of concrete by using recycled micropowder loaded with chemical admixtures and concrete prepared by using the same. The present application uses recycled micropowder after carbonization treatment of waste concrete to load sodium alginate and melamine, which act on different stages of concrete plastic change / cement hydration, reduce early water seepage, late water seepage and promote uniform distribution of water and solid phases, which can significantly improve the color difference of the appearance of concrete after demolding (especially large-flow concrete), improve the overall color consistency of concrete structures, and also play a positive role in promoting the disposal of construction solid waste.
[0008] A method for improving concrete color difference by using recycled micropowder loaded with chemical admixtures is characterized by comprising the following steps: adding recycled micropowder loaded with chemical admixtures according to 1% to 10% of the mass of concrete cementitious materials, mixing with cement, and using it in the preparation and production of concrete;
[0009] The above-mentioned regenerated micropowder loaded with chemical admixtures includes regenerated micropowder loaded with melamine and regenerated micropowder loaded with sodium alginate;
[0010] The above-mentioned regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate are used in a ratio of (1-9): (1-9). In the ratio of sodium alginate to melamine, if sodium alginate: melamine is greater than 9:1, that is, the amount of sodium alginate is too much, or if sodium alginate: melamine is less than 1:9, that is, the amount of melamine is too much, both of which may cause the time for sodium alginate or melamine to play a role in water retention and promoting uniform phase to be too concentrated. Before the concrete solidifies and hardens, due to the difference in solid phase particles and water density, there is always a tendency for solid-liquid phase separation. Therefore, the specific ratio of sodium alginate to melamine is designed to promote uniform distribution of phases throughout the whole process of concrete solidification and hardening.
[0011] The preparation of the above-mentioned recycled fine powder loaded with chemical admixtures includes the following steps: (1) crushing and screening treatment: the waste concrete is crushed and screened to obtain recycled concrete fine powder with a size of less than 0.16 mm; (2) carbonization treatment: the recycled concrete fine powder is placed in a carbonization box for carbonization treatment; (3) loading treatment: part of the recycled concrete fine powder after carbonization treatment is ultrasonically mixed with a melamine solution and part of it is ultrasonically mixed with a sodium alginate solution for loading; (4) drying treatment: the recycled fine powder after loading treatment is dried to constant weight.
[0012] The carbonization box environment in the above step (2) is a carbon dioxide concentration of 20±3%, a relative humidity of 70±5% and a temperature of 20±2° C. The specific operation of the carbonization treatment is: the recycled concrete powder in step (1) is evenly spread in an open tray (material layer thickness 600-800 mm), put into the carbonization box, take out after carbonization for 24 hours, and repeat the above carbonization process after evenly stirring.
[0013] Preferably, the concentration of the melamine solution is 1%, and the ratio of recycled concrete powder to melamine solution is 1:1; the concentration of the sodium alginate solution is 10%, and the ratio of recycled concrete powder to sodium alginate solution is 1:1. Excess melamine solution or sodium alginate solution can also be used to ultrasonically mix with recycled concrete powder, and then filter out excess solution before drying.
[0014] The ultrasonic frequency of the above step (3) is 19.5-20.5 KHz. After ultrasonic dispersion and mixing, the mixture is placed in an environment evacuated to below 10 mbar for 2 hours. Vacuum adsorption can increase the solid loading and solid loading efficiency of the admixture on the recycled concrete powder.
[0015] The temperature of the melamine solution and the sodium alginate solution in the above step (3) is 60° C.; the drying temperature in the above step (4) is 45±2° C. The purpose of drying is to remove moisture and better retain the loaded additives.
[0016] A method for preparing recycled concrete comprises the following steps: uniformly mixing recycled micropowder loaded with melamine and recycled micropowder loaded with sodium alginate; stirring and uniformly mixing the mixed micropowders with cement, fine aggregate, coarse aggregate, water and a dispersant, and pouring the concrete to obtain the concrete.
[0017] The dosage ratio of the above-mentioned recycled micro powder loaded with chemical admixture, cement, fine aggregate, coarse aggregate, water and dispersant is.
[0018] The mixing time of the above-mentioned regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate is not less than 0.5h.
[0019] The concrete obtained by the above preparation method significantly improves the color difference of the appearance of the concrete after demolding, and improves the overall color consistency of the concrete structure.
[0020] Compared with the prior art, this application has the following advantages:
[0021] (1) The recycled micropowder particles have a large number of interconnected pores and cracks. On the one hand, the large specific surface area of the recycled micropowder can absorb excess free water soon after concrete mixing. On the other hand, it can be used as a porous mineral carrier to load specific chemical admixtures and play a slow release role during concrete preparation.
[0022] (2) Sodium alginate loaded in the recycled micropowder can gradually dissolve in free water after concrete mixing. The dissolution process is affected by the porous morphology of the recycled micropowder and proceeds slowly. As cement hydration proceeds, Ca 2+ The concentration gradually increases, cross-linking with sodium alginate to form a hydrogel, which can absorb excess free water using the three-dimensional network structure;
[0023] (3) The melamine loaded in the regenerated micropowder can gradually dissolve in the free water after concrete mixing. The dissolution process is affected by the porous morphology of the regenerated micropowder and progresses slowly. As cement hydration proceeds, the alkalinity in the free water increases and tends to be stable (pH about 13.0). Under the action of strong alkali, melamine is hydrolyzed to form cyanuric acid, which reacts with the further dissolved melamine to form nano-scale supramolecular precipitation, further limiting the uneven precipitation of free water in local micro-regions in the microstructure of cement hydration products.
[0024] (4) The main action process and mechanism of the present invention are as follows Figure 1 As shown in the figure, from the time dimension, the above different effects correspond to different stages of concrete plastic change / cement hydration: the large specific surface area and porous structure of the recycled micropowder can physically adsorb free water at the beginning of concrete mixing, which roughly corresponds to the stage when the concrete has greater fluidity (about 0-2h); as the cement hydrates, the Ca in the system 2+As the concentration increases gradually, it can cross-link with sodium alginate and further adsorb excess free water, which roughly corresponds to the stage when cement hydration begins to accelerate (about 2-4h). Furthermore, as cement accelerates hydration, the pH value in the system increases and stabilizes, and melamine dissolves, hydrolyzes, reacts, and precipitates, filling in the local micro-areas of the hydration product skeleton, promoting the uniform distribution of water and solid phase in the microstructure, and playing a major role before the final setting of the concrete (about 4h to final setting). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the main action process and mechanism of this application;
[0026] Figure 2 This is the appearance diagram of the concrete of Example 1;
[0027] Figure 3 This is the appearance of the concrete of Comparative Example 1;
[0028] Figure 4 This is the appearance diagram of the concrete of Example 2;
[0029] Figure 5 This is the appearance of the concrete of Comparative Example 2;
[0030] Figure 6 This is the appearance diagram of the concrete of Example 3;
[0031] Figure 7 This is the appearance picture of the concrete of comparative example 3;
[0032] Figure 8 This is the appearance diagram of the concrete of Comparative Example 4;
[0033] Fig. 9 This is the appearance picture of the concrete of comparative example 5;
[0034] Fig.10 This is the appearance picture of the concrete of Comparative Example 6;
[0035] Fig.11 This is the appearance picture of concrete of comparative example 8. DETAILED DESCRIPTION
[0036] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The preparation of recycled micropowder loaded with chemical admixtures comprises the following steps: (1) crushing and screening treatment: the waste concrete is crushed and screened to obtain recycled concrete micropowder with a particle size of less than 0.16 mm; (2) carbonization treatment: the recycled concrete micropowder in step (1) is evenly spread in an open tray (material layer thickness 600-800 mm), placed in a carbonization box, taken out after carbonization for 24 hours, and the above carbonization process is repeated after evenly stirring; the carbonization box environment is a carbon dioxide concentration of 20%, a relative humidity of 70% and a temperature of 20°C; (3) loading treatment: part of the recycled concrete micropowder after carbonization treatment is ultrasonically mixed with a melamine solution (60°C) at an ultrasonic frequency of 20 KHz; part of the recycled concrete micropowder is ultrasonically mixed with a sodium alginate solution (60°C) at an ultrasonic frequency of 20 KHz; after ultrasonic dispersion and mixing, it is placed in an environment evacuated to a vacuum of less than 10 mbar and maintained for 2 hours; (4) drying treatment: the recycled micropowder after loading treatment is dried at a drying temperature of 45°C to constant weight.
[0038] The regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate were uniformly mixed according to proportion for 1 hour.
[0039] In the preparation process of the recycled micropowder loaded with chemical admixtures, if the recycled concrete micropowder that has undergone the same carbonization treatment is first ultrasonically mixed with a sufficient amount of saturated melamine solution, and then ultrasonically mixed with a sufficient amount of saturated sodium alginate solution, placed in an environment evacuated to below 10mbar, kept for 2 hours, and then the excess solution is filtered out; and then dried at a drying temperature of 45°C to constant weight. In this way, the relative amounts of melamine and sodium alginate in the concrete preparation process cannot be guaranteed, and the effect of improving color difference cannot be effectively guaranteed.
[0040] In order to evaluate the improvement effect of the recycled micropowder loaded with admixtures in this application on the color difference of concrete, the concrete was prepared and cured and tested by the following methods: according to GB 50081-2002 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete", several cubic specimens of 100mm×100mm×100mm were made respectively, and after curing for 28 days, they were placed in an environment of 20±2℃ and relative humidity of 50%±5% until the surface water vapor dissipated; the non-molding surface of the specimen was placed horizontally in a fixed position under a constant light source, and the camera was set with uniform sensitivity, shutter, aperture and white balance parameters, and side photos of the specimen with a resolution of not less than 3968×2976 pixels were taken for comparison.
[0041] The concrete mix ratio is shown in Table 1, unit: kg / m 3, P·O42.5 cement is used, fine aggregate is natural sand (Zone II medium sand), and dispersant is polycarboxylic acid water reducer with a water reduction rate of not less than 25%. Cement, recycled micro powder loaded with chemical admixtures, fine aggregate, coarse aggregate, water and dispersant are forced to stir in a mixer for 3 minutes, and then molded.
[0042] Table 1
[0043]
[0044]
[0045] Test Example 1: Concrete Performance Test
[0046] According to GB / T 50080-2016 "Standard for Test Methods of Ordinary Concrete Mixture Performance" and GB / T 50081 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the slump, air content and 28d compressive strength were tested. The test results are shown in Table 2 below:
[0047] Table 2
[0048] serial number Slump / mm Gas content / % 28d compressive strength / MPa Example 1 180 2.4% 50.3 Comparative Example 1 180 2.5% 49.8 Example 2 195 2.6% 48.6 Comparative Example 2 205 2.5% 49.2 Example 3 230 2.3% 46.5 Comparative Example 3 240 2.0% 47.0 Comparative Example 4 230 2.1% 46.3 Comparative Example 5 225 2.1% 45.8 Comparative Example 6 225 2.2% 47.2 Comparative Example 7 / / / Comparative Example 8 155 2.3% 48.3
[0049] Table 2 shows the test results of fresh concrete performance and compressive strength prepared according to various embodiments and comparative examples. From the data in the table, it can be found that after the recycled fine powder loaded with chemical admixture replaces cement at 1% to 10% of the mass of the cementitious material, the slump of the high-fluidity mixture is slightly reduced, and the air content and compressive strength are not significantly affected. Figure 2-11 The following are comparison pictures of the color difference of concrete appearance of each group. It can be found that the method described in this application can significantly improve the color difference of concrete appearance after hardening with different fluidity. In particular, from the comparison between Example 3 and Comparative Examples 3 to 6, it can be found that when the recycled micropowder is loaded with chemical admixtures to improve the color difference of concrete, the physical adsorption of the recycled micropowder itself and the reaction of the two chemical admixtures have a positive effect on improving the color difference. Abandoning any of these three phases cannot achieve the best effect. According to Comparative Example 7 (total amount of recycled concrete micropowder, sodium alginate, and melamine is 40kg / m 3 , accounting for 10% of the mass of concrete cementitious materials) the recycled concrete powder, sodium alginate and melamine were directly added to the concrete preparation process, the prepared concrete mixture lost fluidity quickly, and it was even impossible to measure the working performance results and prepare the compressive strength test pieces; Comparative Example 8 (the total amount of recycled concrete powder, sodium alginate, melamine was 4kg / m 3 , accounting for 1% of the mass of concrete cementitious materials) by adding recycled concrete powder, sodium alginate and melamine directly into the concrete preparation process, the prepared concrete mixture has a slight loss of fluidity and a slightly reduced compressive strength.
[0050] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for improving concrete color difference by using recycled micropowder loaded with chemical admixtures, characterized in that: The method comprises the following steps: adding the recycled micro powder loaded with chemical admixtures according to 1% to 10% of the mass of concrete cementitious materials together with cement and mixing them for use in the preparation and production of concrete; The regenerated micropowder loaded with chemical admixtures includes regenerated micropowder loaded with melamine and regenerated micropowder loaded with sodium alginate; The ratio of the regenerated micropowder loaded with melamine to the regenerated micropowder loaded with sodium alginate is (1-9): (1-9).
2. The method according to claim 1, characterized in that The preparation of the regenerated micropowder loaded with chemical admixtures comprises the following steps: (1) Crushing and screening treatment: the waste concrete is crushed and screened to obtain recycled concrete powder with a size of less than 0.16 mm; (2) Carbonization treatment: the recycled concrete powder is placed in a carbonization box for carbonization treatment; (3) Loading treatment: part of the recycled concrete powder after carbonization treatment is ultrasonically mixed with a melamine solution and part of it is ultrasonically mixed with a sodium alginate solution for loading; (4) Drying treatment: the recycled powder after loading treatment is dried to a constant weight.
3. The method according to claim 2, characterized in that: The carbonization box environment in step (2) is a carbon dioxide concentration of 20±3%, a relative humidity of 70±5% and a temperature of 20±2°C.
4. The method according to claim 2, characterized in that: The concentration of the melamine solution is 1%, and the ratio of recycled concrete powder to the melamine solution is 1:1; the concentration of the sodium alginate solution is 10%, and the ratio of recycled concrete powder to the sodium alginate solution is 1:
1.
5. The method according to claim 2, characterized in that: The ultrasonic frequency in step (3) is 19.5-20.5 KHz.
6. The method according to claim 2, characterized in that: The temperature of the melamine solution and the sodium alginate solution in step (3) is 60°C.
7. The method according to claim 2, characterized in that: The drying temperature in step (4) is 45±2°C.
8. A method for preparing concrete, characterized in that: The following steps are involved: Evenly mixing the regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate; After mixing, the mixture is stirred and mixed evenly with cement, fine aggregate, coarse aggregate, water and dispersant, and then poured to obtain the mixture; the regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate are the regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate according to any one of claims 1 to 7.
9. The preparation method according to claim 8, characterized in that: The mixing time of the regenerated micropowder loaded with melamine and the regenerated micropowder loaded with sodium alginate is not less than 0.5h.
10. A concrete, characterized in that: The concrete is prepared by the preparation method according to any one of claims 8 to 9.
Citation Information
Patent Citations
Concrete cementing material, high-durability fair-faced concrete and preparation method thereof
CN107365120A